2013
DOI: 10.1371/journal.pone.0077283
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signatures of Triatomine Vectors of Trypanosoma cruzi Unveiled by Metabolomics

Abstract: Chagas disease is a trypanosomiasis whose causative agent is the protozoan parasite Trypanosoma cruzi, which is transmitted to humans by hematophagous insects known as triatomines and affects a large proportion of South America. The digestive tract of the insect vectors in which T. cruzi develops constitutes a dynamic environment that affects the development of the parasite. Thus, we set out to investigate the chemical composition of the triatomine intestinal tract through a metabolomics approach. We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 68 publications
1
16
0
1
Order By: Relevance
“…Our results are in agreement with recent findings regarding the metabolic environment in the gut of the insect host where a reduced availability of oxygen implies anaerobic fermentation of glucose and amino acid carbon sources. Interestingly, His is the predominant free amino acid in the triatomine feces (33), which correlates with our results showing that His uptake and its metabolism is increased in SPE as a metabolic adaptation under nutritional starvation.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with recent findings regarding the metabolic environment in the gut of the insect host where a reduced availability of oxygen implies anaerobic fermentation of glucose and amino acid carbon sources. Interestingly, His is the predominant free amino acid in the triatomine feces (33), which correlates with our results showing that His uptake and its metabolism is increased in SPE as a metabolic adaptation under nutritional starvation.…”
Section: Discussionsupporting
confidence: 92%
“…Are demonstrated that XD is a useful tool to detect living T. cruzi in persons with CChD [ 46 ], therefore the positivity of PCR-XD and qPCR-XD suggests the presence of viable tripomastigotes naturally amplified by the biological vector. Nevertheless, diverse factors must be considered in the sensitivity of XD: number of boxes used, patient age, capacity of ingestion by the bugs [ 3 , 12 , 24 , 49 ], strong diuresis of triatomines with loss of initial inoculum after a large blood meal [ 14 , 32 ], complexity of the fecal metabolome of triatomines that suggests that it may affect triatomine competence for specific T. cruzi strains [ 1 ], bacterial microbiota in the triatomine gut [ 27 ]; influence of starvation in the development of T. cruzi in Tr. infestans [ 31 ], mortality during the incubation period and differential regulation of parasite populations that shows that some triatomine defense reactions discriminate not only between molecular signals specific for trypanosome infections but also between different strains of T. cruzi [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Epimastigotes in the early exponential growth phase ( in vitro ) are equipped with the complete set of glycolytic enzymes and, in fact, they obtain energy from glucose catabolism. However, it is not known if this is possible inside the insect midgut, since relevant quantities of free sugars in this environment have not been demonstrated so far [ 271 ]. However, the availability of amino acids has been well demonstrated [ 272 , 273 ] and the ability of epimastigotes to catabolize these metabolites is well understood, as previously described.…”
Section: Non-obvious Roles Of Amino Acidsmentioning
confidence: 99%